The chalk girl eaudiobook Kathleen mallory series, book 10. - O'Connell, Carol (Kathleen Mallory, 2012)
New York Times best-selling author Carol O'Connell has won a wide fan base with her popular novels starring NYPD detective Kathy Mallory. in The Chalk Girl, a little girl is abandoned in Central Park-her uncle's body in a tree not far away. Recognizing a kindred spirit in the girl, Mallory takes the case. But her investigation soon leads to a trail of murder and blackmail spanning 15 years. ". a rich, character-driven series ."-Library Journal